A RARE CASE REPORT OF NON - PANCREATIC INTRA - PERITONEAL PSEUDOCYST - Gupta, Rajat (GMC Patiala Journal of Research and Medical Education, 2024)
INTRODUCTION Non-pancreatic pseudocysts are lesions usually arising from mesentery or omentum and are a rare occurrence. The internal content of these cysts could be blood, pus, serous or chylous fluid. In majority of the scenarios, causation of these cysts is related to trauma, surgery or infection. Pseudocysts related to pancreatitis occur in 5 – 15 % of patients who have peripancreatic fluid collection after an episode of acute pancreatitis. It takes at least 4 – 8 weeks for fibrotic reaction to develop and hence for the formation of cyst capsule which is composed of collagen and granulation tissue and is not lined by a true epithelial lining. CASE PRESENTATION A 31year old male presented in surgery OPD with chief complaints of gradually progressive abdominal distension associated with pain epigastrium for past 2 ½ months with intermittent vomiting for past 2 months. There was a positive history of addiction to alcohol, tobacco chewing, and opium was present. On examination, there was a large ill-defined solitary swelling present in left side of abdomen extending approx. 6 cm above and approx. 7 cm below the umbilicus. On head raising test swelling disappeared indicating intraperitoneal origin. USG whole abdomen revealed a large midline septated fluid collection extending from epigastrium to infra-umbilical region with heterogeneous internal echoes with few thin internal septations. CECT whole abdomen showed a large well-defined thick-walled fluid density cystic lesion in the peritoneal cavity few partial thin septations and was seen involving the omentum. CONCLUSION Non pancreatic pseudocyst is a rare finding and one should be aware of this entity.